Consumer preferences towards broadband internet services: a study in Kota Bharu, Kelantan / Meor Hazwan Mat Hassan - Mat Hassan, Meor Hazwan (2011)
The aim of this study was to examine the consumer preferences impact on choosing broadband internet service by consumer in Kota Bharu. There are four (4) independent variables that been studied, which were price, service quality, brand image and promotion. This study also was conduct to examine the most factor from consumer preferences that consumer choose when they want to buy the broadband internet services. Moreover, questionnaires had been used in order to get feedback from consumers. Researcher had distributed 90 questionnaires to consumer around Kota Bharu. The sampling is convenient sampling. The method that been use are simple convenient sampling. The data collected was then tested on its frequency and reliability analysis, regression analysis and Pearson correlation analysis were used to test the hypothesis in this study. The finding on reliability was excellent and it considers that all dependent are acceptable. The findings of this paper suggest four factors are significant factors for explaining consumer preferences. Based from the results obtained in this study, researcher suggests some recommendations to make sure the broadband internet service providers can improve and increase their efforts to meet the requirements of consumer when they want to buy products